Thiết kế và tổ chức dạy học chủ đề “Các hình khối trong thực tiễn” (Toán 8) theo định hướng giáo dục STEM - Hoa Ánh Tường, Hoa Ánh Tường; Nguyễn Võ Anh Thư Nguyễn Võ Anh Thư; Nguyễn Minh Khang, Nguyễn Minh Khang (Tạp chí Giáo dục, 2024)
With the requirements for innovation in teaching according to the 2018 General Education Program, the role of teachers must shift strongly from the position of “teacher” to the position of “organizer, inspector, orientator” of students’ learning activities, implementing more effectively and thoroughly the requirements of the “learning by doing” teaching method. This study presents the process of building STEM lessons and the process of teaching STEM lessons, illustrating this process through teaching the STEM lesson on the topic “Shapes in practice” (Math 8). Organizing STEM lessons with visual, vivid images suitable for students’ level is an opportunity to help them develop their ability to think positively and proactively seek ways to solve problems. Real-life situations are included in class to help students feel interested, arouse their love and passion for mathematics and know how to apply the knowledge they have learned into practice.